IOT-Based Indoor Sensing for Occupancy Detection (International Journal of Innovative Research in Computer Science & Technology, 2019)
In the current generation, Internet of  Things (IOT) has an important role to play in each  and every area. There are many applications of IOT.  One of the most important and efficient applications  is in Home Automation. Consider a scenario of a  building caught on fire, where one need to evacuate  people from an emergency exit. Here, the problem is  that one does not know how many people are present  inside the building in order to evacuate them. In such  cases, home automation plays a very important role.  Occupancy Detection is one such area where one can  sense the presence of a people in a room or a  building. One of the ways of achieving Occupancy  Detection is by Indoor Sensing. This paper proposes  how to attain count of people present inside a room  or a building at particular instant of time with the  help of Infrared (IR) Sensors, finds out current  temperature of a room or a building using  Temperature Sensor and also activates an alarm  when the room is caught on fire with the usage of  Smoke Sensor and Buzzer.
Keywords: Internet of Things; Indoor Sensing; Occupancy Detection; Infrared Sensor; emperature Sensor; Smoke Sensor; Buzzer